1992
DOI: 10.1111/j.1600-0714.1992.tb01366.x
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of oral leukoplakia and lichen planus in diabetes mellitus

Abstract: The occurrence of oral leukoplakia and lichen planus in 1600 patients with diabetes mellitus (815 type 1: insulin-dependent, 761 type 2: non-insulin-dependent)-under care at the International Medicine Department-was studied. Precancerous lesions and conditions were diagnosed and grouped according to internationally accepted criteria. The prevalence of oral leukoplakia in diabetic patients was 6.2%, as compared to 2.2% in the healthy controls, that of oral lichen was 1.0% in the test-, and 0.0% in the control g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
41
3
8

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(57 citation statements)
references
References 23 publications
5
41
3
8
Order By: Relevance
“…Albrecht et al (16) found leukoplakia in 6.2% of their diabetes patients, whereas in the present study, an incidence of 6% for leukoplakia in diabetic patients was observed. Of the l6 precancerous lesions that were screened out, 4 proved to be erythroplakia, i.e., 2% of the 200 diabetes patients.…”
Section: Diabetes Screening Of Oral Cancer Patientscontrasting
confidence: 52%
See 1 more Smart Citation
“…Albrecht et al (16) found leukoplakia in 6.2% of their diabetes patients, whereas in the present study, an incidence of 6% for leukoplakia in diabetic patients was observed. Of the l6 precancerous lesions that were screened out, 4 proved to be erythroplakia, i.e., 2% of the 200 diabetes patients.…”
Section: Diabetes Screening Of Oral Cancer Patientscontrasting
confidence: 52%
“…Considering the well-known oral manifestations of diabetes (11)(12)(13)(14)(15)(16), both the inflammatory processes (gingivitis, periodontitis) and the atrophic lesions (chronic cheilitis and glossitis) are possible precursors of malignant epithelial transformation. However, the epidemiological relationship between these two important diseases has not been studied until now.…”
Section: Diabetes Screening Of Oral Cancer Patientsmentioning
confidence: 99%
“…In agreement with Gusberti et al 57 the findings of our study 53 Type 1 DM to increase the prevalence and severity of periodontitis independent of the effects of oral hygiene, and duration time of DM. 42 However the severity of periodontal disease increased with the duration of DM only among those with an adequate level of oral hygiene (OHI-S = 0) The association between periodontal disease and the duration of diabetes mellitus is consistent with trends seen in other complications of DM whereas the longer duration of diabetes mellitus is in direct proportion of the prevalence and severity of periodontal disease. The development of systemic complications of diabetes such as retinopathy, nephropathy, is also is relationship with the duration of diabetes mellitus agreement with Rylander 58 , Galea et al 59 , Rosenthal et al 60 On the other hand, the presence of severe periodontal infection may also increase the risk for microvascular and macrovascular complications.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmsupporting
confidence: 64%
“…[38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56][57] Individuals with DM tend to have a higher prevalence of periodontal diseases and more severe and rapidly progressing forms than those who do not have DM. 41,48 DM is a known risk factor for periodontitis in adults.…”
Section: Risk Factor Influence On Periodontitis In Type 1 Dmmentioning
confidence: 99%
“…The relationship between diabetes and oral lichen planus and dental caries is less obvious; several studies have shown widely diverging results. [4][5][6][7] A few studies have suggested that decrease salivary flow results from the use of certain drugs, which would result in changes within the mouth, leading to caries, periodontal disease, and soft tissue alterations; the latter may foster invasion by opportunistic microorganisms. Several types of drugs may cause a subjective feeling of dry mouth, or may induce low salivary flow; these include anticholinergics, antidepressants, diuretics, antihistamines, myorelaxants, diazepinic drugs, and sympatheticomimetics such as hypotensive drugs.…”
Section: Introductionmentioning
confidence: 99%